If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18m + 9 = 3(4m + -9) Reorder the terms: 9 + 18m = 3(4m + -9) Reorder the terms: 9 + 18m = 3(-9 + 4m) 9 + 18m = (-9 * 3 + 4m * 3) 9 + 18m = (-27 + 12m) Solving 9 + 18m = -27 + 12m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-12m' to each side of the equation. 9 + 18m + -12m = -27 + 12m + -12m Combine like terms: 18m + -12m = 6m 9 + 6m = -27 + 12m + -12m Combine like terms: 12m + -12m = 0 9 + 6m = -27 + 0 9 + 6m = -27 Add '-9' to each side of the equation. 9 + -9 + 6m = -27 + -9 Combine like terms: 9 + -9 = 0 0 + 6m = -27 + -9 6m = -27 + -9 Combine like terms: -27 + -9 = -36 6m = -36 Divide each side by '6'. m = -6 Simplifying m = -6
| (x-7)(4)=0 | | 23-x=275 | | -0.6c-7=6 | | 3-5x-7x=87 | | 14x-3=9x+5 | | 168=19-v | | 2+e=-2 | | ln(5x)+ln(10x)= | | 3(5x+3)=-5(5x-2) | | v+60=5v | | 3x+90=126 | | 6x=9y-6 | | 0.6(b-4)=-9 | | 8x-2y=41 | | 1.82= | | x(x+12)=(x-4)(x-4) | | ln(5x)+ln(10x)=4 | | 4-v=265 | | 6x+9y=65 | | Y-4+7y=24 | | -16=-4+4y | | y-7.2=9 | | 8x-(11x-9)=24-3x | | X-17=3Y-17 | | a+5=6a | | 75+2y=42 | | 3v=v+38 | | 40.00+19.25x=69.25+16.00x | | ln(7)+ln(x+3)=0 | | y=2x-(-3) | | 9cot^2-3=0 | | 5(3n+1)=7(4n+5)+5 |